Business Environment Reforms in Fragile and Conflict-Affected Situations : What Works and Why? - Ghossein, Tania; Rana, Ahmed Nauraiz (World Bank, Washington, DC, 2022)
Economies that are suffering from fragility, conflict and violence (three distinct yet interconnected elements of FCS) confront intractable poverty, and faltering growth – missing out on development objectives by significant margins. As the poverty rate in FCS has increased, the number of poor people in those economies has increased from 180 million to nearly 300 million – almost at par with the number of poor in non-FCS economies (which constitute 90 percent of global population). It is estimated that by 2030, two-thirds of the global poor will be concentrated in fragile states. This means that ending extreme poverty requires accelerating gains where poverty has been most intractable: in FCS. By definition, the economies concerned are often characterized by weak institutions and political instability, and lower level of private sector development to promote business-led growth. FCS economies require significant reforms to policy and delivery mechanisms along multiple dimensions to achieve growth and poverty reduction.